Mycoplasma decontamination in Chlamydia trachomatis culture: a curative approach. Issue 9 (16th December 2021) - Greer, Madison; Elnaggar, Jacob H; Taylor, Christopher M; Shen, Li
Abstract: Mycoplasma contamination of cell culture represents a serious problem in research and decontamination from cell-propagated obligate intracellular bacteria has proven challenging. Here, we presented an optimized protocol to remove Mycoplasma from contaminated Chlamydia trachomatis culture. A stepwise procedure of Mycoplasma removal entails (i) incubation in nonionic detergent-containing solution and (ii) separation of viable chlamydial organisms by fluorescence-activated cell sorting (FACS), followed by subcloning using a focus-forming assay. We also adapted a polymerase chain reaction (PCR) assay using paired universal and Mycoplasma -specific primers, which are distinguishable from the C. trachomatis counterparts, in combination with Sanger sequencing to determine the presence of mycoplasmas' 16S rRNA genes. These integrated approaches allow for full removal of Mycoplasma, as verified by the improved PCR assay, without compromising the capacity of viable C. trachomatis to adapt to new infection in epithelial cells. Some pitfalls during the Mycoplasma decontamination process are discussed. Abstract : An integrated, stepwise procedure allows for full removal of Mycoplasma from contaminated Chlamydia culture.